Evaluation of the effectiveness of low-dose aspirin and omega 3 in treatment of asymmetrically intrauterine growth restriction: A randomized clinical trial. (March 2017) - Ali, Mohammed K.; Amin, Maggy E.; Amin, Ahmed F.; Abd El Aal, Diaa Eldeen M.
Abstract: Objective: To test the effect of aspirin and omega 3 on fetal weight as well as feto-maternal blood flow in asymmetrical intrauterine growth restriction (IUGR). Study design: This study is a clinically registered (NCT02696577), open, parallel, randomized controlled trial, conducted at Assiut Woman's Health Hospital, Egypt including 80 pregnant women (28–30 weeks) with IUGR. They were randomized either to group I: aspirin or group II: aspirin plus omega 3. The primary outcome was the fetal weight after 6 weeks of treatment. Secondary outcomes included Doppler blood flow changes in both uterine and umbilical arteries, birth weight, time and method of delivery and admission to NICU. The outcome variables were analyzed using paired and unpaired t -test. Results: The estimated fetal weight increased significant in group II more than group I (p = 0.00). The uterine and umbilical arteries blood flow increased significantly in group II (p < 0.05). The birth weight in group II was higher than that observed in group I (p < 0.05). Conclusion: The using of aspirin with omega 3 is more effective than using aspirin only in increasing fetal weight and improving utero-placental blood flow in IUGR.